The degree of Organizational Health availability and its relationship to Job Performance among workers in the Ministry of Education in the Sultanate of Oman - Radhiya Al-Habsi; Jokha Al-Swafi (Umm Al-Qura University, 2023)
The current study aimed to determine the degree of organizational health availability and its relationship to job performance among workers in the Ministry of Education in the Sultanate of Oman. And to identify whether there are statistically significant differences at the level of significance (05≥ α) between the arithmetic averages due to the study variables (gender, occupational position, and years of experience in the field of the current job). To achieve the aims of the study, the study used the correlative descriptive approach, in order to answer its questions, a study scales was developed; the first measures the degree of organizational health availability, while the second measures job performance. The results were as follows: The degree of organizational health in the Ministry of Education in the Sultanate of Oman was "large". Where the dimensions of organizational independence and organizational cohesion each scored a high degree, while the dimension of institutional integrity achieved a medium degree and the level of job performance among workers in the Sultanate of Oman was high in all its dimensions. There are no statistically significant differences at the level of significance (05≥ α) in the responses of the study sample members to the degree of organizational health, and the level of job performance due to the variables: gender, occupational position, and years of experience. The results also showed a strong positive correlation between organizational health and job performance among workers in the Ministry of Education in the Sultanate of Oman. The study recommended Preparing professional meetings and seminars among the employees of the directorates of the Ministry's general office; to discuss the dimensions of organizational health, and its impact on the job performance of teachers and enhancing the level of institutional integrity in the departments of the educational directorates in the Ministry's general office.